Fjölmenning á Íslandi Maí 2018 - Esja Jeanne Jónsdóttir 1989- (2018)
In Icelandic the word menning (culture) does not exist in the plural form – yet at the same time Icelandic society is more multicultural than it has ever been. The focus in this project is on Icelanders who have one parent of foreign origin. Nine individuals from different backgrounds, cultures and generations talk about the “other culture” they grew up in, and their experience of being half-foreign in their own country. How does an individual perceive his/her surroundings when he/she is brought up in two different cultures? The five senses are employed in recounting that experience. The project comprises a folder of different portraits to which new information and new individuals can be added, almost indefinitely.